Pendampingan Pengelolaan Lingkungan Masjid Miftahul Jannah - Adeswastoto, Hanantatur; Aswara, Dana; Afrila, Esa (Journal of Social and Community Service, 2023)
This activity aims to help manage the environment around the Miftahul Jannah Mosque through a participatory approach. Education and direct practice on waste management and greening are carried out together with residents around the mosque. The problems faced by partners are the low awareness of the congregation regarding the importance of maintaining environmental cleanliness and the suboptimal waste management system. The activity is carried out through initial observation, preparation of educational materials, socialization, and field practice that directly involves the community. The community service team consists of lecturers and students of the Civil Engineering Study Program, Pahlawan Tuanku Tambusai University, with support from the local village government. The results of the activity show an increase in community understanding and participation in maintaining the mosque environment. Most participants began to implement the habit of disposing of garbage in its place, caring for plants, and being active in discussions and mutual cooperation activities. The impact of this activity is not only seen from changes in behavior, but also the formation of a collective spirit in maintaining the cleanliness of worship facilities. This activity proves that an educational and participatory approach is effective in increasing community awareness of the environment. It is hoped that this activity can become a model for community-based environmental management that can be replicated in other areas with similar problems.